2019
DOI: 10.3389/fpsyg.2019.02293
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Individual Differences in Executive Function and Theory of Mind in Relation to Prejudice Toward Social Minorities

Abstract: Executive function (EF) and theory of mind (ToM) are key cognitive skills for socio-emotional adjustment. Executive function develops considerably between 3 and 7 years of age, and fosters the development of social cognition skills such as ToM. Studies with adults have shown a link between EF and prejudice, as well as between empathy and prejudice. Moreover, the relationship between EF, cognitive and affective ToM and prejudice has barely been studied in children. In this study, we aimed at examining the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 84 publications
1
15
0
1
Order By: Relevance
“…With increasing social-cognitive development, prejudice may decrease further during adolescence or may increase again due to socialization factors. Aboud’s ideas regarding the influence of social-cognitive development on prejudicial attitudes in young children have continued to be confirmed by recent studies (e.g., Hoyo et al, 2019; Johnson & Aboud, 2017; Raabe & Beelmann, 2011). Aboud and Johnson (Aboud, 2008; Johnson & Aboud, 2012, 2017) explain these prejudicial attitudes in young children as due to children’s social-cognitive developmental levels, which results in their difficulty in recognizing and reconciling differences in people—abilities that require executive functioning (EF) and theory of mind (ToM).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…With increasing social-cognitive development, prejudice may decrease further during adolescence or may increase again due to socialization factors. Aboud’s ideas regarding the influence of social-cognitive development on prejudicial attitudes in young children have continued to be confirmed by recent studies (e.g., Hoyo et al, 2019; Johnson & Aboud, 2017; Raabe & Beelmann, 2011). Aboud and Johnson (Aboud, 2008; Johnson & Aboud, 2012, 2017) explain these prejudicial attitudes in young children as due to children’s social-cognitive developmental levels, which results in their difficulty in recognizing and reconciling differences in people—abilities that require executive functioning (EF) and theory of mind (ToM).…”
Section: Discussionmentioning
confidence: 87%
“…Aboud and Johnson (Aboud, 2008; Johnson & Aboud, 2012, 2017) explain these prejudicial attitudes in young children as due to children’s social-cognitive developmental levels, which results in their difficulty in recognizing and reconciling differences in people—abilities that require executive functioning (EF) and theory of mind (ToM). Hoyo et al (2019) have shown that EF and ToM scores are negatively correlated with prejudicial attitudes, that is, the better children’s EF and ToM abilities, the less prejudicial attitudes they hold. Children in the 4 to 7 age range generally lack conservation skills and first- and second-order ToM skills (Jackson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… Number of studies included in systematic review, based on cool and hot executive functions analyzed. Working Memory ( n = 24): (Bock et al, 2015 ; Kennedy et al, 2015 ; Kharitonova et al, 2015 ; Lee Swanson et al, 2015 ; Rajan and Bell, 2015 ; Roberts et al, 2015 ; Bellaj et al, 2016 ; Lagattuta et al, 2016 , 2018 ; Pailian et al, 2016 ; Vogan et al, 2016 ; Barriga-Paulino et al, 2017 ; Barry et al, 2018 ; Goriot et al, 2018 ; Lensing and Elsner, 2018 ; Ludyga et al, 2018 ; Matte-Gagné et al, 2018 ; Nys et al, 2018 ; Simms et al, 2018 ; Wilson et al, 2018 ; Yang and Merrill, 2018 ; Hoyo et al, 2019 ; Lecce et al, 2019 ; Plebanek and Sloutsky, 2019 ). Inhibitory Control ( n = 19): (Bock et al, 2015 ; Kennedy et al, 2015 ; Rajan and Bell, 2015 ; Aïte et al, 2016 ; Bellaj et al, 2016 ; Lagattuta et al, 2016 , 2018 ; Steinbeis et al, 2016 ; Symeonidou et al, 2016 ; Hao, 2017 ; Mahy et al, 2017 ; Mous et al, 2017 ; Arbel et al, 2018 ; Barry et al, 2018 ; Goriot et al, 2018 ; Matte-Gagné et al, 2018 ; Simms et al, 2018 ; Wilson et al, 2018 ; Hoyo et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive Flexibility ( n = 10): (Bock et al, 2015 ; Chevalier and Blaye, 2016 ; Erb et al, 2017 ; Goriot et al, 2018 ; Ludyga et al, 2018 ; Matte-Gagné et al, 2018 ; Perone et al, 2018 ; Simms et al, 2018 ; Wilson et al, 2018 ; Hoyo et al, 2019 ). Theory of Mind ( n = 16): (Bock et al, 2015 ; Bulgarelli et al, 2015 ; Chaplin and Norton, 2015 ; Gómez-Garibello and Talwar, 2015 ; Kennedy et al, 2015 ; Lagattuta et al, 2016 , 2018 ; Symeonidou et al, 2016 ; Wang et al, 2016 ; Hayward and Homer, 2017 ; Mahy et al, 2017 ; Brandone and Klimek, 2018 ; Holl et al, 2018 ; Wilson et al, 2018 ; Hoyo et al, 2019 ; Lecce et al, 2019 ). Delay of Gratification ( n = 3): (Steinbeis et al, 2016 ; Hao, 2017 ; Wilson et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have covered this issue, focusing on teachers themselves, considering both their personal characteristics and the teaching methodologies used [1]. In this way, the investigation into the influence of psychological and behavioural characteristics of students who share a classroom with special educational needs (SEN) students has been put on the back burner [2]. However, these characteristics are related to issues of great current relevance, such as school bullying [3,4].…”
Section: Introductionmentioning
confidence: 99%